Effect of different shading on the growth performance of roselle (Hibiscus sabdariffa L.) seedlings - Siti Nur Sarah, bt Abdull Razak (Universiti Malaysia Sarawak (UNIMAS), 2012)
Roselle (Hibiscus sabdariffa. Linn.) is commonly called Jamaica sorrel, Indian sorrel or red sorrel, is a dicotyledonous and autogamous plant cultivated in tropical and subtropical regions for its fleshy calyces, seeds, leaves and stems. Roselle is probably a native of West Africa and is now widely cultivated throughout the tropics and subtropics e.g. Sudan, China, Thailand, Egypt, Mexico and the West India (El-saidy et aI., 1992). According to Cobley (1968), the crop is cultivated throughout the India subcontinents, part of Asia, America, Australia and throughout Africa. However, the crop is most suited to tropical climates such as Malaysia.